Menggali makna kewirausahaan dalam pendidikan akuntansi: Perspektif mahasiswa AM terhadap kurikulum MBKM dan SDG 8 - Umi Nuraini; Sulikah Sulikah (Jurnal Pendidikan Ekonomi (JUPE), 2025)
The digital transformation and the requirements of SDG 8 have necessitated the incorporation of entrepreneurship into higher education, particularly in accounting education. The MBKM program is a strategic initiative aimed at enhancing experiential learning; nevertheless, research investigating student experiences in this setting is still few. A qualitative phenomenological approach indicates that student participation in the AM program enhances awareness and interest in entrepreneurial professions, especially as edupreneurs.  Field activities improve interpersonal skills, including communication, collaboration, and leadership. Students believe that the incorporation of entrepreneurship into the curriculum is not comprehensive, hindered by insufficient infrastructure support, a scarcity of lecturer role models, and a rigid academic culture.  This study underscores the significance of a transformational and interdisciplinary methodology in accounting education to cultivate an adaptive entrepreneurial ecosystem. Practical implications urge higher education institutions to enhance assistance for the cultivation of entrepreneurial competencies to facilitate the attainment of SDG 8.